Quantification of liver fat content in liver and primary liver lesions using triple-echo-gradient-echo MRI. - Nougaret, Stephanie; Monsonis, Benjamin; Molinari, Nicolas; Riviere, Benjamin; Piron, Lauranne; Kassam, Zahra; Cassinotto, Christophe; Guiu, Boris (European Radiology, 2020)
Objectives: To quantify and compare the fat fraction of background liver and primary liver lesions using a triple-echo-gradient-echo sequence. M&M: This IRB-approved study included 128 consecutive patients who underwent a liver MRI for lesion characterization. Fat fraction from the whole lesion volume and the normal liver parenchyma were computed from triple-echo (consecutive in-phase, opposed-phase, in-phase echo times) sequence.Results: Forty-seven hepatocellular carcinoma (HCCs), 25 hepatocellular adenomas (HCAs), and 56 focal nodular hyperplasia (FNH) were included. The mean intralesional fat fraction for various lesions was 7.1% (range, 0.5-23.6; SD, 5.6) for HCAs, 5.7% (range, 0.8-14; SD, 2.9) for HCCs, and 2.3% (range, 0.8-10.3; SD, 1.9) for FNHs (p = 0.6 for HCCs vs HCA, p < 0.001 for FNH vs HCCs or HCA). A fat fraction threshold of 2.7% enabled distinction between HCA and FNH with a sensitivity of 80% and a specificity of 77%. The mean normal liver parenchyma fat fraction was lower than the intralesional fat fraction in the HCC group (p = 0.04) and higher in the FNH group (p = 0.001), but not significantly different in the HCA group (p = 0.51).Conclusion: Triple-echo-gradient-echo is a feasible technique to quantify fat fraction of background liver and primary liver lesions. Intralesional fat fraction obtained from lesion whole volume is greater for HCCs and HCA compared to FNH. When trying to distinguish FNH and HCA, an intralesional fat fraction < 2.7% may orient toward the diagnosis of FNH.Key Points: • Triple-echo technique is feasible to quantify intralesional fat fraction of primary liver lesions. • Whole volume intralesional fat fraction is greater for HCCs and HCA compared to FNH. • An intralesional fat fraction < 2.7% may orient toward the diagnosis of FNH.